Healing the enduring wound of cartesian dualism through embodied rootedness - Hannah R. Bacon (Rivista Internazionale di Filosofia e Psicologia)
In this article I will take up the interlocking themes of breath, Cartesian dualism, and the transparent body as they are articulated in The healing body: Creative responses to illness, aging, and affliction by Drew Leder. Through an expansive reading of the breath as spirit, I contend that we can arrive at a body-concept that is still expansive and open to the world, but does not require the intermediary step of the renunciation of or distancing from the body. This preserves the porous and intersubjective openness that characterize Leder’s conception of the “transparent body” but puts more daylight between the “transparent body” and what he terms the “absent body”. My aim is to extend the metaphor of this embodied expansiveness to think through instances in which the body is interconnected but still manifestly consciously foregrounded, rooted, and felt.